Argentina's (macroeconomic?) trap: Some insights from an empirical stock-flow consistent model - Sebastian Valdecantos (Levy Economics Institute of Bard College, 2020)
The Argentinean economy has just ended another lost decade. After the peak registered in 2011, the per capita GDP has oscillated with a decreasing trend, leaving the economy poorer than it was ten years before. During these ten years, different governments with conflicting macroeconomic programs were in power, none of them able to save the economy from stagflation. The goal of this paper is to address to what extent the economic performance would have been better had other policy combinations been implemented. The analysis is made through an empirical quarterly stock-flow consistent (SFC) model for the period 2007-19 in order to ensure the coherence of the results and to give the outcomes of the simulations a holistic and dynamically consistent interpretation. From the results of the simulations it seems that the problem that is keeping Argentina in stagflation goes beyond the domain of macroeconomics. The fact that in practice two divergent macroeconomic programs were implemented-neither of them being able to produce good and sustainable macroeconomic performance-is a first symptom that favors the case for that hypothesis. When the model is used to counterfactually test the policy recommendations of these approaches with the external conditions that prevailed while the opposite program was implemented, none of them yield results that can be deemed sustainable. Yet, the model developed in this paper can be useful for studying the different policy combinations that, given a specific context, can bring about more stable and sustainable dynamics for the Argentinean economy.
Keywords: C54; E17; E61; E65; 330; Stock-Flow Consistent Models; Argentina; Economic Policy